All Saint's Anglican Church in Aklavik, NWT ... - Farnel, Sharon (University of Alberta Library, 2017)
All Saint's Anglican Church in Aklavik is a part of the Anglican Diocese of the Arctic. It was built on the site of the Cathedral of the Diocese, which burned in 1974. ...